'Ripple' effect on infant zBMI trajectory of an internet‐based weight loss program for low‐income postpartum women. Issue 1 (17th September 2018) - Phelan, S.; Hagobian, T. A.; Ventura, A.; Brannen, A.; Erickson‐Hatley, K.; Schaffner, A.; Muñoz‐Christian, K.; Mercado, A.; Tate, D. F.
Summary: Background: Weight loss interventions can have positive 'ripple' effects on untreated partners in the home, but ripple effects on infants are unknown. Objective: To examine whether a 12‐month internet‐based weight loss intervention for postpartum mothers had a positive ripple effect on participants' infants. Methods: A 12‐month cluster randomized, assessor‐blind, clinical trial enrolling 371 postpartum women at 12 Women, Infants, Children clinics in CA. Clinics were randomized to standard Women, Infants, Children or an internet‐based weight loss intervention for mothers. Results: A total of 333 of the 371 (89.8%) mothers assented for infant participation. Infants were 5.3 ± 3.2 months; 75.9% were Hispanic and 64% were breastfeeding. Infant retention was 272/333 (82.7%) at 6 months post enrollment and 251/333 (75.3%) at 12 months post enrollment. In intent‐to‐treat analysis, a significant interaction between group and time was observed ( p = 0.008) with the offspring of intervention mothers exhibiting lower zBMI change from study entry through 6 months (0.23 [CI, 0.03, 0.44] vs. 0.65 [0.50, 0.79] zBMI change, respectively; p = 0.001) but was not significant through 12 months ( p = 0.16). Regardless of group, maternal reports at the final assessment indicated that infants (aged =17.2 ± 3.4 months) consumed sweetened beverages (0.93 ± 1.5/week), juice (2.0 ± 1.4/day), 'junk food' (7.8 ± 5.4/week) and fast food (2/month), and 46.7% of the infants had a TV in their bedroom. Conclusions: An internet‐based weight loss program for low‐income, postpartum mothers had a positive 'ripple' effect on the zBMI of infants in the home during the first 6 months of treatment.